2015
DOI: 10.1371/journal.pone.0126084
|View full text |Cite
|
Sign up to set email alerts
|

Bat-Fruit Interactions Are More Specialized in Shaded-Coffee Plantations than in Tropical Mountain Cloud Forest Fragments

Abstract: Forest disturbance causes specialization of plant-frugivore networks and jeopardizes mutualistic interactions through reduction of ecological redundancy. To evaluate how simplification of a forest into an agroecosystem affects plant-disperser mutualistic interactions, we compared bat-fruit interaction indexes of specialization in tropical montane cloud forest fragments (TMCF) and shaded-coffee plantations (SCP). Bat-fruit interactions were surveyed by collection of bat fecal samples. Bat-fruit interactions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Sturnira and Carollia species produced similar seed germination probability in Piper species. Dietary studies on Sturnira in montane forests have shown that Sturnira consume Piper fruits in the same magnitude as their supposedly preferred Solanum fruits (Hernández-Montero et al 2015, Castaño et al 2018. These results suggest that in montane forests where Carollia species abundance decreases, Sturnira species provide compensatory seed dispersal services to Piper plants.…”
Section: Is Seed Germination Dependent On Bat Dietary Preferences?mentioning
confidence: 82%
See 1 more Smart Citation
“…Sturnira and Carollia species produced similar seed germination probability in Piper species. Dietary studies on Sturnira in montane forests have shown that Sturnira consume Piper fruits in the same magnitude as their supposedly preferred Solanum fruits (Hernández-Montero et al 2015, Castaño et al 2018. These results suggest that in montane forests where Carollia species abundance decreases, Sturnira species provide compensatory seed dispersal services to Piper plants.…”
Section: Is Seed Germination Dependent On Bat Dietary Preferences?mentioning
confidence: 82%
“…Dietary studies on Sturnira in montane forests have shown that Sturnira consume Piper fruits in the same magnitude as their supposedly preferred Solanum fruits (Hernández‐Montero et al. , Castaño et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…It is distributed from the north of México to the northwest of Ecuador and west of Colombia, in South America and lives mainly in wooded areas, in an altitudinal range that goes from 300 to 2,130 m (Webster and Jones 1982). This species is locally common in central Veracruz, México (Castro-Luna and Galindo-González 2012), and it is known that in Mesoamerica it feeds mainly of the Moraceae and Solanaceae families (Hernández-Conrique et al 1997;García-Estrada et al 2012;Hernández-Montero et al 2015), although along its distribution range consumes fruits from plants of 13 taxonomic families: Actinidiaceae, Campanulaceae, Cannabaceae, Euphorbiaceae, Gesneriaceae, Hypericaceae, Lamiaceae, Melastomataceae, Muntingiaceae, Myrtaceae, Piperaceae, Rosaceae and Urticaceae (Lobova et al 2009;Hernández-Montero et al 2015;Castaño et al 2018).…”
mentioning
confidence: 99%
“…Phyllostomid frugivorous bats have developed remarkable plasticity in their use of food resources, but a few plant families make up the core of their diet throughout the year (Hernández-Montero et al 2015;Sánchez and Giannini 2018). However, rare situations such as the supplementary consumption of insects during critical stages of nutrient demand (Orr et al 2016), or the ingestion of pollen, leaves or fruits with ornitochorous characteristics (e.g., red or purple color), may also occur (Galleti and Morellato 1994;Castro-Luna and Sosa 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation